2016
DOI: 10.1093/jisesa/iev157
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genome ofBrachmia macroscopa(Lepidoptera: Gelechiidae) and Its Related Phylogenetic Analysis

Abstract: The sweet potato leaf folder, Brachmia macroscopa, is an important pest in China. The complete mitogenome, which consists of 13 protein-coding genes (PCGs), 22 transfer RNA genes, two ribosomal RNA genes, and an A + T-rich region, was sequenced and found to be 15,394 bp in length (GeneBank no. KT354968). The gene order and orientation of the B. macroscopa mitogenome were similar to those of other sequenced lepidopteran species. All of the PCGs started with ATN as the canonical start codon except for cox1, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The PCR reaction systems contained 0.2 µL of rTaq (TaKaRa Co., Dalian, China; see Gu et al ., ), 1.0 µL DNA template, 2.5 µL 10_rTaq buffer (Mg 2+ free), 2.5 µL 25 m m MgCl 2 , 2.0 µL dNTPs, and 0.5 µL of each primer, with the following cycling parameters: 5 min at 94°C, followed by 35 cycles of 30 s at 94°C, 30 s at 47–58°C, and 1–2.5 min at 72°C, with a subsequent 10‐min final extension at 72°C. To avoid poor Sanger sequence qualities due to inadvertent amplification of multiple products (nontarget binding of primers), PCR products were separated by electrophoresis on a 1.0% agarose gel and gel purified using a DNA Gel Extraction Kit (Bioteke, Beijing, China; see Ma et al ., ). The purified amplicons were sent to Beijing Genomics Institute (Shenzhen, China) for sequencing.…”
Section: Methodsmentioning
confidence: 97%
“…The PCR reaction systems contained 0.2 µL of rTaq (TaKaRa Co., Dalian, China; see Gu et al ., ), 1.0 µL DNA template, 2.5 µL 10_rTaq buffer (Mg 2+ free), 2.5 µL 25 m m MgCl 2 , 2.0 µL dNTPs, and 0.5 µL of each primer, with the following cycling parameters: 5 min at 94°C, followed by 35 cycles of 30 s at 94°C, 30 s at 47–58°C, and 1–2.5 min at 72°C, with a subsequent 10‐min final extension at 72°C. To avoid poor Sanger sequence qualities due to inadvertent amplification of multiple products (nontarget binding of primers), PCR products were separated by electrophoresis on a 1.0% agarose gel and gel purified using a DNA Gel Extraction Kit (Bioteke, Beijing, China; see Ma et al ., ). The purified amplicons were sent to Beijing Genomics Institute (Shenzhen, China) for sequencing.…”
Section: Methodsmentioning
confidence: 97%
“…Such damage leads to considerable quantitative and qualitative economic losses and usually infested seeds never germinate (Crombie 1943;Yang et al 2012). Prior to this study, mitochondrial genome of seven species have been sequenced in the Gelechiidae family (Ma et al 2016;Park et al 2016;Ram ırez-R ıos et al 2016). Here, we have sequenced the complete mitochondrial genome of S. cerealella based on the samples collected from Huaxi District in Guizhou, China (geographic coordinate: N26 23 0 41.1394571745972 00 , E106 40 0 46.096659178428 00 ), which would facilitate our understanding of the mitochondrial genome, phylogeography and the phylogenic relationship of the Gelechiidae family.…”
mentioning
confidence: 99%
“…The larvae frequently cause extensive damage to their host crops and result in serious economic loss to the growers. Our previous studies have involved determining the complete mitochondrial genomes of this pest, as well as detailed research on the developmental and fecundity responses of the species under different temperatures to identify the most susceptible phase of its development and growth 12,13 . Additionally, based on a two-year field investigation in Changsha, China, we found that local B. macroscopa fed mainly on three Convolvulaceae plants, sweet potato vine Ipomoea batatas (L.) Lam., Chinese waterspinach I. aquatica Forsskål, and Japanese morning glory Pharbitis purpurea (L.) 14 .…”
Section: Introductionmentioning
confidence: 99%